Do anxiety or determination of life differ based on the perceived financial status to cope with severe diseases?. (April 2019) - Lee, E.; Cho, J.
Abstract: Objective: The objective of this study was to identify the relationships among people's perceived financial status to cope with severe disease, levels of anxiety and determinations of life. Study design: This is a secondary analysis of population-based cross-sectional surveys. Methods: The 2016 Social Integration Survey of 8000 Korean participants aged 19 years or older was used. Data were analysed using correlation, correspondence and covariate analyses. Results: Of all the participants, 84.6% responded that they had insufficient perceptions of financial status; decision-making power was found to have a stronger correlation with perceived financial stability than with real income. In addition, the perceived ability, based on financial status, to cope with severe disease was correlated with anxiety. Conclusions: The study proposes that when developing health and medical treatment policy and intervention programmes, perceptions of personal financial status and stability should be considered concurrently. Highlights: The associated factors with perceived financial status to cope with severe disease are assessed. Survey data of 8000 Koreans older than 19 years are used. Data are analysed through correlation, correspondence and covariate analyses. Decision-making has a greater correlation with perceived financial status than income. Perceived financial status should be considered in intervention design.